Does The Characteristic Of The Supervisory Board Affect Audit Quality? - Anak Agung Putu Gede Bagus Arie Susandya; Ni Nyoman Ayu Suryandari (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The purpose of this study is to find empirical evidence of the effect of independence, work experience, professional ethics, motivation, and professional expertise on the audit quality of the Supervisory Board in LPD located at Denpasar-Bali. Lembaga Perkreditan Desa (LPD) is the financial institution based on local culture. They grow rapidly because of emotional bond with their customer. The LPD was formed because of the common desire to encourage the economic progress of the village where they live based on local wisdom. The population is collected from all LPD registered in Denpasar. The total number of respondents of this study is 99, with multiple regression analysis is used. The results of this study finds that independence, work experience, and professional skills do not affect the audit quality of supervisory board. The supervisory board has a great social responsibility in the existence of the LPD. Professional ethics and motivation positively have an important role influencing the audit quality of supervisory board. As the LPD only have a governor regulation, the supervisory board is the important key to keep an eye of the LPD’s performance. LDP as an economic cultural heritage must always maintain the trust of the local community.